KNOWLEDGE TRANSFER AND TEACHING IN FIRST AID AND PREHOSPITAL CARE IN THE ENGINEERING COURSES - Rosângela de França Bail,; João Luiz Kovaleski,; Daiane Maria de Genaro Chiroli,; Vander Luiz da Silva, (Revista Eletrônica Científica Ensino Interdisciplinar, 2020)
This study"™s purpose is to present a case report, developed in a higher education institution in Brazil and centered on spreading knowledge about first aid among a group of Engineering students, offering a perspective of prevention regarding dangers and hazards in general. It analyzes a project at the Federal University of Technology - Paraná, in Brazil, involving students in engineering courses. The central modules approached are: basic concepts of first aid; clinical emergency; convulsive crisis, intoxication and sudden onset; fractures, hemorrhage control and immobilization of the injured; and burns, bandages, and transportation of the injured. Thus, in times of accidents, while specialized help goes to the place in need, these students become able to apply the knowledge acquired.